Constitutional Thinness and Anorexia Nervosa: A Possible Misdiagnosis? - Estour, Bruno; Galusca, Bogdan; Germain, Natacha (Frontiers in Endocrinology, 2014)
Clinical and biological aspects of restrictive anorexia nervosa (R-AN) are well documented. More than ten thousand articles since 1911 and more than six hundred in 2013 have addressed R-AN psychiatric, somatic and biological aspects. Genetic background, ineffectiveness of appetite regulating hormones on refeeding process, bone loss and place of amenorrhea in the definition are widely discussed and reviewed. Oppositely, constitutional thinness (CT) is an almost unknown entity. Only 32 articles have been published on this topic since 1953. Similar symptoms associating low BMI, low fat and bone mass are reported in both CT and R-AN subjects. Conversely, menses are preserved in CT women and almost the entire hormonal profile is normal, except for leptin and PYY. The aim of the present review is to alert the clinician on the confusing clinical presentation of these two situations, a potential source of misdiagnosis, especially since R-AN definition has changed in DSM-5.